PEMAHAMAN PEMUDA TERHADAP MAKNA KEBAKTIAN MINGGU GEREJA PRESBYTERIAN INJILI INDONESIA JEMAAT SOLA SCRIPTURA MEDAN - Sampitmo Habeahan; Yakobus Ndona; Liber Siagian (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2021)
The objective of this research is to find out how the level of youth understanding about the meaning of Sunday service in Indonesia Evangelical Presbyterian Church (GPII) Sola Scriptura Medan. This research is descriptive it means that the result of the study describe what is in according to the result of the study. Research finding based on the result of observations and interviews concluded that most of the youths have been seriously followed and been active in the Sunday service but there are a few the youths whispered, talked, went in and out of the church when worship taking place. This is in accordance with the result of processed data netted using a closed questionnaire instrument which concluded that 6.3 % of the research subjects were in the very good category, 58,8 % were in good category and there were 45.15 % were in the bad or bad category. Therefore, the tendency of youth to understand the elements of the meaning of the Sunday service is likely to conclude well. The result of the study indicate the importance of more serious coaching for youth, namely in the form of religious education in schools, fostering parents in the family and supervision of church council when worship taking place.